Berchemia sessiliflora (Rhamnaceae) is Bridelia tomentosa (Phyllanthaceae) - Deng, Yunfei (Phytotaxa, 2020)
Berchemia sessiliflora was originally described in the family Rhamnaceae from Hong Kong, China, and the identity remained uncertain since being published. Examination of type material reveals that it is well identical with Bridelia tomentosa of Phyllanthaceae, a species widely distributed in tropical and subtropical regions of Asia and Australia.